Norfloxacin-Loaded Lipospheres: A Novel Lipid-Based Approach for Enhanced Solubility, Stability and Bioavailability - Tanwar, Rajni; Singh Brar, Arshdeep; Gulati, Puja (Journal of Neonatal Surgery, 2025)
Norfloxacin, a second-generation fluoroquinolone exhibits potent antibacterial activity but suffers from poor oral bioavailability due to limited solubility, permeability and extensive first-pass metabolism. Liposphere-based drug delivery systems offer a promising approach to overcoming these limitations by encapsulating norfloxacin in lipid matrices enhancing its solubility, stability and controlled release. This review explores the formulation strategies, characterization and evaluation of norfloxacin-loaded lipospheres. Various preparation techniques including solvent evaporation, melt dispersion and supercritical fluid technology are discussed highlighting their impact on encapsulation efficiency, particle size and drug release kinetics. The pharmacokinetic advantages of lipospheres including improved absorption, prolonged systemic circulation and reduced dosing frequency are analyzed through in vitro and in vivo studies. Furthermore, the potential clinical applications of lipospheres in bacterial infections, their safety considerations and future prospects in lipid-based antibiotic delivery are examined. Lipospheres present a viable strategy for enhancing norfloxacin’s therapeutic effectiveness, minimizing bacterial resistance and improving patient compliance. Further research into stability optimization, large-scale production and clinical validation is warranted to facilitate the transition of liposphere-based formulations into mainstream pharmaceutical applications.